2002
DOI: 10.1080/01650250143000229
|View full text |Cite
|
Sign up to set email alerts
|

Oral language and reading abilities of first-grade Peruvian children: Associations with child and family factors

Abstract: T his study investigated the relationship between selected child and family demographic characteristic s (child age, child sex, child birth order, maternal education, and parent language status), family processes (parent-to-child reading at home, and parent expectations about child's educational attainment), and preschool experience with poor Peruvian rst-grade children's oral language and reading abilities, and examined whether those factors help to explain differences among children living in poverty. First-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…When mothers support their children, the children are likely to achieve better academic outcomes. These data coincide with findings reported in other studies carried out with Latin American children in their hometowns regarding the value of family support actions and the mother's motivation and interest in the student's education (Barber, 1988;Bazán, Castellanos, & López, 2010;Castro, Lubker, Bryant, & Skinner, 2002;Mella & Ortiz, 1999). Similarly, in the United States, despite involvement barriers, Latin American mothers have developed activities and experiences to support and reinforce their children's learning, which positively influences the educational process (Kreider, 2011;Quiñones, 2009;Salinas-Sosa, 1997).…”
Section: Discussionsupporting
confidence: 81%
“…When mothers support their children, the children are likely to achieve better academic outcomes. These data coincide with findings reported in other studies carried out with Latin American children in their hometowns regarding the value of family support actions and the mother's motivation and interest in the student's education (Barber, 1988;Bazán, Castellanos, & López, 2010;Castro, Lubker, Bryant, & Skinner, 2002;Mella & Ortiz, 1999). Similarly, in the United States, despite involvement barriers, Latin American mothers have developed activities and experiences to support and reinforce their children's learning, which positively influences the educational process (Kreider, 2011;Quiñones, 2009;Salinas-Sosa, 1997).…”
Section: Discussionsupporting
confidence: 81%
“…This can be explained by the fact that mothers involve themselves significantly more in reading-related activities with their firstborns than with their subsequent children (Castro et al 2002;Raikes et al 2006;Westerlund and Lagerberg 2008). This was also the case in our study: firstborns received more maternal teaching of letters and reading and were read to more often than other children.…”
Section: Mothers' Reading-related Activities and Children's Reading Ssupporting
confidence: 51%
“…Birth order may also influence the development of children's literacy. Castro et al (2002) showed that Grade 1 students who are firstborns are better at letter-word identification and at reading comprehension than students born later: this relates to the fact that parents tend to devote more time at home to parent-child reading with their firstborns than with their subsequent children (see also Raikes et al 2006;Westerlund and Lagerberg 2008). Gender also plays a role when learning literacy.…”
mentioning
confidence: 94%
“…In addition, parents encouraged their children to retell the stories after watching television, an activity that can be said to influence oral language (Castro, Lubker, Byrant, & Skinner, 2002;Dickinson & Tabors, 2001;Isbell, Sobol, Lindauer, & Lowrance, 2004;Schneider, 1996). The differences in the way the children experienced literacy in their families can be explained as a consequence of parental attitudes, and this could be noted from the way the parents facilitated the organization and structuring of the physical and social contexts (DeBaryshe, 1995;Reese & Gallimore, 2000).…”
Section: Discussionmentioning
confidence: 99%